Analisis Pengaruh Word Of Mouth Terhadap Keputusan Nasabah Untuk Menabung Dengan Brand Equity Sebagai Variabel Mediasi Pada PT. Bank Syariah Indonesia (BSI) Kantor Cabang Perdagangan - Fani, Meiti; Nurbaiti, Nurbaiti; Nasution, Juliana (LPPM Universitas Labuhanbatu, 2023)
This study aims to examine the influence of word of mouth analysis on the customer's decision to save with brand equity as a mediation variable at PT. Bank Syariah Indonesia (BSI) trading branch offices either partially or simultaneously, and also in path analysis. This study uses quantitative methods with data collection using likert scale method. Subjects used in this study are customers of PT. Bank Syariah Indonesia (BSI) trading branch offices totaling 100 people and taken by using probability sampling. Data analysis techniques through IBM SPSS statistical program 25. The results of this study show that. First, Word of Mouth has a positive and significant effect on customer decisions with a significant value of 0.026 0.05. Second, Word of Mouth has a positive and significant effect on brand equity with a significant value of 0.000 0.05. Third, brand equity has a positive and significant effect on customer decisions with a significant value of 0.008 0.05. And, fourth, word of mouth indirectly affects the customer's decision to save through brand equity as a mediation variable with the value of indirect influence greater than direct influence.